2018
DOI: 10.1080/1478422x.2017.1374049
|View full text |Cite
|
Sign up to set email alerts
|

High temperature oxidation of 9–12% Cr ferritic/martensitic steels under dual-environment conditions

Abstract: In normal operations, the opposite surfaces of the power plant components are exposed to two different environments, i.e. air/flue gas on the one side and steam on the other side. Exposure under such dual-environment can lead to accelerated corrosion of the components on the air side. The oxidation behaviour of ferritic/martensitic steel T92 was investigated under dual-environment in a specially designed test equipment. The samples were exposed to dry oxyfuel flue gas (CO 2-27%N 2-2%O 2-1%SO 2) on one side and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The dual atmosphere gained widespread attention in the context of SOFC almost two decades ago [10] and has been extensively explored ever since [11][12][13][14][15][16][17]. Although many mechanistical aspects of the dual atmosphere effect are not completely understood, a number of firm experimental facts were established: (i) hydrogen from the fuel side dissolves in the steel, migrates to the air side and disrupts protective scaling of Cr 2 O 3 [13,17]; (ii) the dual atmosphere effect diminishes with increasing temperature being most intense at 600 °C [14]; (iii) Cr evaporation on the air side may additionally undermine the protectiveness; however, it is not the primary reason of the effect occurring also on the dry air side [14]; (iv) cold-work [51][52][53] such as, e.g., grinding of the air side suppresses the dual atmosphere effect.…”
Section: Effect Of Dual Atmospherementioning
confidence: 99%
See 1 more Smart Citation
“…The dual atmosphere gained widespread attention in the context of SOFC almost two decades ago [10] and has been extensively explored ever since [11][12][13][14][15][16][17]. Although many mechanistical aspects of the dual atmosphere effect are not completely understood, a number of firm experimental facts were established: (i) hydrogen from the fuel side dissolves in the steel, migrates to the air side and disrupts protective scaling of Cr 2 O 3 [13,17]; (ii) the dual atmosphere effect diminishes with increasing temperature being most intense at 600 °C [14]; (iii) Cr evaporation on the air side may additionally undermine the protectiveness; however, it is not the primary reason of the effect occurring also on the dry air side [14]; (iv) cold-work [51][52][53] such as, e.g., grinding of the air side suppresses the dual atmosphere effect.…”
Section: Effect Of Dual Atmospherementioning
confidence: 99%
“…Work by Yang et al [10] showed that oxidation under such dual atmosphere conditions differs from oxidation in single atmosphere, i.e., the same atmosphere on both sides. This finding spurred a lot of work on this field resulting in somewhat contradictory results [11][12][13][14][15][16][17]. Nevertheless, it is nowadays firmly established that the dual atmosphere effect is real and recent work by Gunduz et al [17,18] explains how different parameters influence the effect and thus shedding light on the discrepancies reported in the literature.…”
Section: Introductionmentioning
confidence: 99%